Intercultural practices in experiential rural tourism, case of an Andean community on the shores of Lake Titicaca in Puno, Perú - Mamani-Flores, Adderly; Huaracha-Velasquez, Jaime; Morales-Quispe, Erich Feliciano; Cotrado-Lupo, Sheylla Lía; Maquera-Maquera, Yuselino; Calatayud-Mendoza, Alfredo Pelayo; Mamani-Flores, David Josué; Mamani-Flores, Ruben Sandino (Edelweiss Applied Science and Technology, 2024)
The practice of experiential rural tourism involves the active participation of the local population, promoting cultural exchange between visitors and residents generating intercultural relationships. The objective of the research was to analyze the intercultural relationships that are established between local inhabitants and tourists in the practice of experiential rural tourism. The factors that were analyzed are communication, mutual respect, socioeconomic development, cultural authenticity, shared cultural practices, reciprocity, valuation of cultural identity and the environment in the perceptions and experiences of tourists and local residents. The qualitative approach and method was used, the techniques applied were the in-depth interview with the local population and tourists, direct observation of the practice of this activity and content analysis. The results revealed that there are intercultural relations due to the direct and meaningful interaction between tourists and the local population, facilitating the exchange of knowledge, mutual understanding, representation, authenticity and cultural integration, promoting intercultural dialogue as a basis for a more inclusive and responsible tourism, as well as the importance of cultural authenticity in attracting tourists and preserving local identity..